مشيخة العرب والسياسة العثمانية في بايلك قسنطينة - سكاك نسرين; عوايجية بثينة (My University, 2024)
abstract: The Ottomans in Algeria maintained the administrative and social regulations that prevailed before they entered Algeria - even if they changed their names - including the Arab Presbyterian Foundation, which formed one of the most important organs of Ottoman power in the Algerian countryside, particularly the East Baylik chieftaincy. The latter, which shared the rule with Bayat Constantine, revealed to us the dual power between the Turkish rulers in cities and the families in the countryside, and thus the invalidity of the traditional colonial theory aimed at highlighting the flaws of Ottoman rule by its removal from power of Algerian society. The Ottoman rule was confined to the major cities, unlike the countryside, which was essentially controlled by the genetic chieftaincy. The Arab chiefdom, if it is one of the pillars of the Baalk authority in rural areas, is at the same time a manifestation of the political and social formation of Algerian society in the Ottoman period. One of the chiefdoms was to highlight the Arab chiefdom in the Zab region and the eastern Sahara, on which the families of bouakaz and Ben Qanou rotated. These sheikhdoms served as a link between Algerian society in the countryside and the governing authority in the cities until they were linked to the regimes. The extension of State influence within the Algerian countryside was measured by the extent of their allegiance. ------------------------------------- الملخص : لقد احتفظ العثمانيون في الجزائر بالأنظمة الإدارية والإجتماعية التي كانت سائدة قبل دخولهم لها ــ وإن غيروا تسمياتهاــ ومن بين هذه الأنظمة مؤسسة مشيخة العرب التي شكلت أحد أهم أجهزة السلطة العثمانية بالريف الجزائري خاصة منها مشيخة بايلك الشرق. هذه الاخيرة التي كانت تتقاسم الحكم مع بايات قسنطينة، فكشفت لنا عن ثنائية السلطة بين الحكام الأتراك بالمدن و الأسر النافذة بالريف وبالتالي ابطال النظرية الاستعمارية التقليدية الرامية إلى ابراز عيوب الحكم العثماني من خلال ابعاده للمجتمع الجزائري عن السلطة، وهو الأمر الذي اختص به الحكم العثماني في المدن الكبرى على عكس الارياف التي كانت تتحكم فيها المشيخات الوراثية بشكل أساسي، فمشيخة العرب اذا هي إحدى دعائم سلطة البايلك في الفضاءات الريفية وفي نفس الوقت إحدى مظاهر التشكل السياسي والإجتماعي للمجتمع الجزائري في الفترة العثمانية، ومن هذه المشيخات سلطنا الضوء على مشيخة العرب بمنطقة الزاب و الصحراء الشرقية التي تناوب عليها كل من اسرتي بوعكاز وبن ڨانة، هاته المشيخات التي كانت بمثابة حلقة وصل بين المجتمع الجزائري بالريف والسلطة الحاكمة بالمدن حتى ارتبطت بها أنظمة الحكم وأصبح امتداد نفوذ الدولة داخل الريف الجزائري يقاس بمدى ولاء هذه المشيخات لها. ------------------------------------ résume: Les Ottomans en Algérie ont conservé les systèmes administratifs et sociaux qu’ils avaient précédés avant leur entrée – bien que leurs noms aient changé – et parmi ces systèmes, l’institution populaire arabe qui a formé l’un des principaux organes d’autorité ottomane dans la campagne algérienne. Cette dernière, qui partageait le pouvoir avec les Kashmir, nous a révélé le pouvoir bilatéral entre les souverains turcs des villes et les familles rurales et, par conséquent, la théorie coloniale traditionnelle de l’Arabie saoudite a montré les défauts de la domination ottomane dans les espaces ruraux et, en même temps, une manifestation de la formation politique et sociale de la société algérienne dans les grandes villes ottomaniques, ce qui a mis en lumière le problème de la région arabe et du désert oriental, où chaque pays s’est opposé à l’islamisme et à sa domination.
Keywords: مشيخة العرب، السياسة العثمانية، بايلك قسنطينة